Return to work advice after total hip and knee replacement. (3rd February 2020) - Nouri, F; Coole, C; Baker, P; Drummond, A
Abstract: Background: Little is known about the information and advice on return to work received by patients undergoing total hip and knee replacement. Aims: To investigate patients' views and experiences of work-related advice provided by clinicians, and how this might be improved. Methods: Semi-structured interviews with patients who had undergone total hip and knee replacement, were working prior to surgery and intended to return to work. Data were analysed thematically. Results: Forty-five patients from three UK regions were consented. Eight themes were identified including lack of information, lack of an individualized approach and accessibility and acceptability of information dissemination methods. Patients identified their information needs and who they felt was best placed to address them. Conclusions: Patients receive little information and advice on return to work following total hip and knee replacement, although not all patients required this. However, more focus is needed on providing this, and patients should be screened to ensure resources are best targeted with interventions being tailored to the individual.